(untitled) (Research, Society and Development, 2022)
The objective of the present study was to evidence the use of Cannabis Sativa-based drugs, which aims at its benefits and therapeutic action and to report its mechanism of action in the treatment of Depression. The study was developed from an integrative literature review in which books, dissertations, articles and theses that were published between 2005 and 2021 were searched. Documents published in Portuguese and English that were available in the databases were selected. Scielo, CAPES, PUBMED and LILACS journals. In addition to the databases, official documents from PAHO (Pan American Health Organization) and Ministry of Health were used in the construction of this review. Depression is a disabling disease that affects around 350 million people worldwide. Considering that currently available antidepressants take 2 to 4 weeks to take effect, being ineffective in about 40% of cases, new drugs with rapid antidepressant action, such as that observed by CBD, are of great clinical relevance. It was evidenced about the efficiency of medicines based on Cannabis sativa, which is a medicinal plant with pharmacological properties that present effects as close or similar to neuroleptic medicines, whose active principle used for the manufacture of psychoactive medicines is Cannabidiol (CBD) that helps the central nervous system and the body by reducing and alleviating the effects of depression.